Comparing the Sensitivity and Specificity of Zinc Sulphate Flotation Method to Formol Ether Sedimentation Method in Identifying Intestinal Protozoa’s Cysts - Dini Alyani; Elsa Herdiana Murhandarwati; Sri Sumarni; Ernaningsih Ernaningsih (Tropical Medicine Journal, 2013)
ABSTRACTIntroduction: The two main methods to detect the presence of intestinal protozoa’s cysts are zinc-sulphate flotation (Faust’s) and formol-ether sedimentation (Ritchie’s) methods. Some researchers have recommended using both flotation and sedimentation in detecting the intestinal parasites. However, this approach is unpractical for most laboratories. To date there are no studies that conclude which method, either Faust’s method or Ritchie’s method, is more effective in term of sensitivity and specificity of detecting the intestinal protozoa cyst. This study was done to conclude which method has higher sensitivity and specificityObjectives: To compare the sensitivity and specificity of Faust’s to Ritchie’s methods in identifying intestinal protozoa.Methods: Thirty anonymous fecal samples were obtained from Parasitology Laboratory Faculty of Medicine Gadjah Mada University. Each sample was tested using both Faust’s and Ritchie’s methods and then microscopically examined to find the intestinal protozoa’s cysts. Numbers of samples with cyst-positive were recorded to determine which method has higher ability to detect the intestinal protozoa’s cysts. Data was analyzed by calculating sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV).Results: From all the five identified cysts (Entamoeba histolytica, Giardia lamblia, Entamoeba coli, Iodamoeba butschlii, Blastocystis hominis), Ritchie’s method was able to detect more cyst than Faust’s method. The sensitivity and specificity of Ritchie’s method compared to Faust’s were 100% and 93.33% respectively. The positive predictive value (PPV) and negative predictive value (NPV) of Ritchie’s compared to Faust’s method were 93.75% and 100% respectively. Ritchie’s method is proven to have higher sensitivity and specificity than Faust’s method. This method has high sensitivity probably because of the cysts are concentrated and so more cysts could be collected.Conclusion: This study concludes that the Ritchie’s method has higher sensitivity and specificity compared to Faust’s method in detecting five common intestinal protozoa’s cysts.Keywords: formol-ether sedimentation method, zinc-sulphate flotation method, intestinal protozoa, sensitivity, specificity.